Pengaruh Literasi Keuangan, Pendapatan, Prilaku Keuangan dan Gaya Hidup terhadap Kesejahteraan ASN (Aparatur Sipil Negara) Dinas Pendidikan Dikabupaten Bondowoso - Amelia Putri Maharani; Ni Nyoman Putu Martini; Achmad Hasan Hafidzi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
In Bondowoso Regency, an interesting phenomenon was discovered regarding the financial condition of State Civil Apparatus (ASN) within the Education Office. Despite having a fixed monthly income, some ASN still face quite complex financial problems. This is caused by uncontrolled consumptive spending patterns, which create a gap between income and expenditure. This research contributes theoretically by enriching the literature on personal financial management and the financial behavior of civil servants. This study specifically aims to analyze the influence of several independent variables—namely, financial literacy, income, financial behavior, and lifestyle—on ASN welfare. The study employs a quantitative method with a saturated sampling technique. From a population of 88 ASN, all were used as research samples to provide more representative data. The analysis process used multiple linear regression with the help of SPSS software. Before conducting the regression analysis, several classical assumption tests were carried out, including the normality test, multicollinearity test, and heteroscedasticity test, to ensure that the statistical model was reliable and free from violations. Next, a t-test was applied to measure the magnitude of the influence of each independent variable on ASN welfare. The results of the study showed differences in the influence of each variable. Two variables were found to have a positive and significant effect on well-being: income and financial behavior. This indicates that better financial behavior and higher income of civil servants (ASN) increase their well-being. On the other hand, financial literacy and lifestyle variables showed a positive but insignificant effect on well-being. This means that although financial literacy and lifestyle contribute, their influence is not strong enough to improve ASN well-being. These findings indicate that income and the ability to manage personal finances play a dominant role in determining ASN well-being in Bondowoso Regency.